The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5194/amtd-8-5677-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-resolution measurements from the airborne Atmospheric Nitrogen Dioxide Imager (ANDI)

Abstract: Abstract. Nitrogen Dioxide is both a primary pollutant with direct health effects and a key precursor of the secondary pollutant ozone. This paper reports on the development, characterisation and test flight of the Atmospheric Nitrogen Dioxide Imager (ANDI) remote sensing system. The ANDI system includes an imaging (UV)-vis grating spectrometer able to capture scattered sunlight spectra for the determination of tropospheric nitrogen dioxide (NO2) concentrations by way of DOAS slant column density and vertical … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The corresponding surface reflectances and viewing and sun geometries recorded by the AirMAP instrument are also provided in the plot, as well as the other RTM parameter settings. A strong dependence of the AMF on the surface reflectance can be observed, consistent with previous studies reported in Lawrence et al (2015), Meier et al (2017), and Tack et al (2017). In the upper panel of Fig.…”
Section: Amf Dependence On Rtm Parameters Amf Dependence On the Surface Reflectancesupporting
confidence: 91%
See 1 more Smart Citation
“…The corresponding surface reflectances and viewing and sun geometries recorded by the AirMAP instrument are also provided in the plot, as well as the other RTM parameter settings. A strong dependence of the AMF on the surface reflectance can be observed, consistent with previous studies reported in Lawrence et al (2015), Meier et al (2017), and Tack et al (2017). In the upper panel of Fig.…”
Section: Amf Dependence On Rtm Parameters Amf Dependence On the Surface Reflectancesupporting
confidence: 91%
“…The majority of these studies have focused on the retrieval of the NO 2 field over urban areas and/or industrial sites, i.e. Heue et al (2008), Kowalewski and Janz (2009), Popp et al (2012), General et al (2014), Lawrence et al (2015), Schönhardt et al (2015), Nowlan et al (2016), Lamsal et al (2017), Meier et al (2017), Tack et al (2017), Vlemmix et al (2017), Broccardo et al (2018), Merlaud et al (2018), and Nowlan et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric in situ measurements or remote sensing scans can be powerful tools to map pollution hot spots (Worden et al, 2013;Kort et al, 2014;Lawrence et al, 2015;Jacob et al, 2016) or identify and quantify larger than expected pollution sources (de Gouw et al, 2009;Karion et al, 2013). Kort et al's (2014) U.S. CH 4 anomaly map relied on retrievals of total column average CH 4 dry air mixing ratio (XCH 4 , hereafter) from near infrared radiance measurements aboard the SCIAMACHY satellite (Frankenberg et al, 2006(Frankenberg et al, , 2011.…”
Section: Background On Four Corners Methane Hot Spotmentioning
confidence: 99%
“…However, satellite instruments have been shown to be capable of observing the downwind plume of large cities (e.g., Beirle et al, 2011Beirle et al, , 2019Lorente et al, 2019). In contrast, airborne imaging spectrometers have inherently much higher spatial resolutions of a few tens of meters and thus can retrieve detailed NO 2 maps for whole cities (Heue et al, 2008;Lawrence et al, 2015;Popp et al, 2012;Schönhardt et al, 2015;Tack et al, 2017;Nowlan et al, 2016;Tack et al, 2019). However, satellite and airborne instruments measure (tropospheric) vertical column densities (VCDs), while near-surface concentrations (NSCs) are the quantity of interest for the assessment of air pollution exposure.…”
Section: Introductionmentioning
confidence: 99%